A randomised control trial into the effects of early lactation foot trimming on the production parameters of Holstein dairy heifers - Maxwell, Oliver J. R. (2016)
Lameness is a painful disease of dairy cattle which has profound effects on production. Despite this, there is surprisingly limited experimental evidence on its prevention or treatment, especially with reference to the non-infectious claw horn lesions. A randomised, negatively controlled trial was conducted to investigate the association between a functional and remedial foot-trim between 50 and 80 days post calving on primiparous animals and production outcomes. 281 heifers were enrolled from 8 farms in the UK and randomly assigned to treatment or control groups. Milk yield (305 day adjusted) was not significantly different between groups (trimmed 7727L, untrimmed 7646L). However, multivariate regression analysis demonstrated that this relationship was confounded by lameness state. Animals which were lame at the time of trimming gave 734L more milk than those which were non-lame and untrimmed. These results suggest that, based on milk production alone, it would not have been cost beneficial to trim all heifers; however a targeted intervention aimed at lame animals would have delivered a substantial return on investment. As a very minimum it is recommend heifers should be regularly assessed in early lactation and treated as soon as they are identifiably lame. The high prevalence of lesions identified suggests routine trimming for all heifers may be justifiable on welfare grounds even if the milk yield benefits are marginal.